The selection of building process according to the inner comparative substantiation control/Baubetriebliche verfahrensauswahl mit vergleichsinternen plausibilitätskontrollen - Müller, Heinz (Journal of Civil Engineering and Management, 1997)
Generally speaking, many technological processes are suitable for implementing definite building tasks, though only one alternative from many other possibilities is preferred. Therefore, the main task of every building enterprise is to find an optimal variant and try to implement it when making preparations for performing building processes. Alternative variants are variants which serve the same purpose and in essence should be able to implement adequate building tasks. A complex comparison of variants may be carried out by many methods. For a practical comparison of processes at a building undertaking, a method is suggested which integrates, in its comparison logaritm, the substantiation control, preserving at the same time logic correctness of separate comparison steps. The selection criteria are obtained depending on particular building tasks and legal aspects. Information faults pertaining to data may cause mistakes when comparing variants. Determination of variant rank sequence is based on the principle of deductive logic according to which a complex problem should be decomposed into partial problems till they become transparent and then can be solved. A successful building process is evaluated as being of 1 rank. The results of calculation are presented in diagrams which make the visual assessment much easier.Statybos proceso parinkimas pagal lyginamą vidinę pagrįstumo kontrolęSantrauka. Tam tikriems statybos uždaviniams įgyvendinti tinka apskritai daugelis technologinių procesų, tačiau iš gausybės galimybių prioritetas suteikiamas tik vienai alternatyvai. Todėl kiekvienos statybos įmonės pagrindinis uždavinys ruošiantis darbui yra rasti tinkamą. optimalų variantą ir koncentruotis jį įgyvendinant. Alternatyvūs variantai yra tie, kurie padeda vienodiems naudojimo tikslams ir iš principo privalo sugebėti įgyvendinti atitinkamus statybos uždavinius. Kompleksinį variantių palyginimą galima atlikti pagal daugelį metodų. Praktiškai statybos įmonei palyginti procesus pristatomas toks metodas, į kurio palyginimo logaritmą integruojama pagrįstumo kontrolė, išsaugant logišką. atskirų palyginimo žingsnių teisingumą. Parinkimo kriterijai gaunami atsižvelgiant į konkrečius statybos uždavinius ir į teisinius aspektus. Informacijos defektai naudojantis duomenimis gali padaryti žalos lyginant variantus. Nustatant variantams rangų eiliškumą, remiamasi deduktyvinės logikos principu, pagal kurį kompleksine problema plačiai suskaidoma į dalines problemas, kol šios pasidaro aiškesnės ir tuomet galima jas išspręsti. Palankus statybos procesas apibūdinamas 1 rangu. Skaičiavimo rezultatai taip pat pateikiami diagramomis, tai dar labiau palengvina vizualų įvertinimą.Article in German.First Published Online: 26 Jul 2012